2024
DOI: 10.1039/d3dt02879h
|View full text |Cite
|
Sign up to set email alerts
|

The anticancer application of half-sandwich iridium(iii) ferrocene-thiosemicarbazide Schiff base complexes

Xicheng Liu,
Ao Lv,
Pei Zhang
et al.

Abstract: Half-sandwich iridium(iii) ferrocene-thiosemicarbazide Schiff base complexes can induce apoptosis of A549 cells through a lysosomal–mitochondrial anticancer channel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…29,30 For example, Liu and co-workers have observed apoptotic cell death mode by ferrocene-based half-sandwich Ir(III) complexes. 39 Similarly, the Chakravarty group has reported the ferrocene conjugates of several first-row transition metal complexes inducing cellular apoptosis under the influence of visible light. 40−42 Also, Meggers and Wilson groups have shown Re(I) tricarbonyl complexes caused apoptosis in cancer cells upon light exposure.…”
Section: In-cell Ros Generation and Change In Mitochondrial Membrane ...mentioning
confidence: 98%
See 3 more Smart Citations
“…29,30 For example, Liu and co-workers have observed apoptotic cell death mode by ferrocene-based half-sandwich Ir(III) complexes. 39 Similarly, the Chakravarty group has reported the ferrocene conjugates of several first-row transition metal complexes inducing cellular apoptosis under the influence of visible light. 40−42 Also, Meggers and Wilson groups have shown Re(I) tricarbonyl complexes caused apoptosis in cancer cells upon light exposure.…”
Section: In-cell Ros Generation and Change In Mitochondrial Membrane ...mentioning
confidence: 98%
“…40 Liu et al have reported the improvement in redox activity and cytotoxicity of half-sandwich Ir(III) complexes due to the presence of the ferrocene moiety (Table 1). 39 The Gasser group has also reported the enhancement in the bioactivity of ferrocene-based anthelmintic praziquantel against HeLa cells. 67 Recently, Patra and co- workers realized the effect of ferrocene moiety conjugation on Ru(II)/Pt(II) complexes to overcome cisplatin resistance and improve its cytotoxicity.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, iridium complexes can target organelles such as mitochondria, lysosomes, and endoplasmic reticulum by regulating their lipophilicity. 3–10 Secondly, due to the strong spin–orbit coupling effect and rich photophysical and chemical properties of cyclometalated iridium( iii ) complexes, they exhibit photodynamic and photothermal activity. 11–17 In addition, iridium complexes can induce multiple modes of cell death, including apoptosis, 18,19 autophagy, 20 oncosis, 21 ferroptosis, 22 pyroptosis, 23 etc .…”
Section: Introductionmentioning
confidence: 99%